AEROBIC AND STRENGTH EXERCISES IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD): A CASE STUDY - Blas, Lara (2016)
This study was aimed at describing the physiological responses of Chronic Obstructive Pulmonary Disease (COPD) patients in each session of an 8-week training program and analyzing its effects on the patients’ physical performance. Four COPD patients (64 ± 6 years) participated in this study. A 6-minute walking test (6MWT) (T1) was performed before the training program to determine the cardiovascular capacity of the participants. After 8 weeks 6MWT was repeated (T2). During the training program participants performed interval aerobic endurance, strength, stretching and respiratory muscle training. There was no significant increase in the physiological variables (systolic and diastolic blood pressure and oxygen saturation) after 6MWT neither in T1 or T2. However, the systolic pressure in the Post test of T1 (∆%=24.8±22.1; ES=2.2, high) and Post test of T2 (∆%=14.0±13.2; ES=1.0, high) reported a tendency to be higher than the Pre test. With respect to physical performance, participants walked slightly more meters after the training sessions (∆%=4.61; ES=0.4, low), which was accompanied by an increased effort perception (∆%=107.1; ES=3.0 and ∆%=200.0; ES=1.8 for RPEmus). Participants slightly improved their physical performance in the 6MWT probably because sessions were not only focused on improving aerobic capacity but also muscle strength.